Effects of Green Tea and Lemon Essential Oil Mouthwashes on Surface Roughness of Resin-Modified Glass Ionomer Cement - Margaretta, Dewi Liliany; Caroline, Caroline (Indonesian Dental Association, 2021)
Introduction: Resin-modified glass ionomer cement (RMGIC) is a restorative material developed with aim to overcome the weaknesses of GIC which has poor physical properties that can affect the surface roughness. A rough surface is a contributing factor to the accumulation of plaque and development of secondary caries. One of the factors that cause surface roughness is the use of mouthwash. Objective: To determine the effect of two essential oil mouthwashes on the surface roughness of RMGIC. Methods: Fifteen samples of RMGIC (cylindrical, 2 mm high and 10 mm in diameter) were divided into three treatment groups (n = 5 in each group). In group I, the samples were immersed in green tea essential oil mouthwash for 30 seconds. In group II, the samples were immersed in lemon essential oil mouthwash for 60 seconds. In group III, the samples were immersed in distilled water (control group). All the samples were immersed for 21 days at room temperature (37°C), with two repetitions. The surface roughness was then tested using a surface roughness tester (Taylor Hobson S100 Series; AMETEK Inc; United States of America). Results: The data were analyzed using one way ANOVA with Tukey’s Post Hoc test (p <0.05). Statistical analysis with One Way ANOVA test indicates a significant change in the value of surface roughness between the three groups. Tukey’s Post Hoc test with p=0.009 shows a significant difference in testing the effect of green tea essential oil mouthwash. Conclusion: Green tea essential oil mouthwash affected the surface roughness of RMGIC compared to lemon essential oil mouthwash. However, both did not have a significant difference with control groups.